PENGARUH TAMBAHAN PENGHASILAN PEGAWAI (TPP) DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN OGAN KOMERING ULU - Martini, Martini; Munajat, Munajat; Kenamon, Mardiah (Forum Bisnis Kewirausahaan, 2024)
The research was conducted at the OKU Regency Tourism and Culture Office. The research method uses quantitative descriptive using multiple linear regression data analysis. Based on the results of the analysis and discussion that has been carried out, it can be concluded that partially Additional Employee Income (X₁) has a significant effect on Employee Performance at the OKU Regency Tourism and Culture Office and the Competency variable (X₂) has a significant effect on Employee Performance at the OKU Regency Tourism and Culture Office. Simultaneously, Employee Income Supplement (X₁) and Competence (X₂) have a significant influence on Employee Performance at the Tourism and Culture Office of OKU Regency. The coefficient of determination (R2) obtained is 0.874. This shows that the contribution of the influence of additional employee income and competence on employee performance is 87.4% while the remaining 12.6% is influenced by other variables not mentioned in this study.